1994
DOI: 10.1002/oms.1210290912
|View full text |Cite
|
Sign up to set email alerts
|

C60‐assisted laser desorption‐ionization mass spectrometry

Abstract: Mass spectrometry is a major growth area in scientific instrumentation utilized in the chemical, biomedical, materials and earth sciences. In general, samples for a mass spectrometer have to be vaporized to allow ionization to take place. 1-5 Kistemaker and co-workers, were the first to demonstrate, using a laser microprobe. the usefulness of laser desorption as an ionization technique for thermally labile high-mass compounds.Laser desorption has been differentiated into the separate ionization techniques refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 20 publications
0
25
0
1
Order By: Relevance
“…The most frequently used matrices are derivatives of benzoic acid, e.g., 2,5-dihydroxybenzoic acid (2,5-DHB; Juhasz et al 1993;Carpentieri et al 2007) and derivatives of cinnamic acid, e.g., α-cyano-4-hydroxycinnamic acid (CHCA) or sinapic acid (SA). Fullerenes have also been used as matrices, whereas the first application was for laser desorption of biomolecules involving application of protein analyte solution directly onto the pre-deposited fullerene film (Michalak et al 1994). Fullerene matrices has been used for MALDI-TOF analysis of small hydrophobic molecules (e.g., steroids, fatty acids; Mernyak et al 2008, Mernyak et al 2009), but until now there are no data reported on their application for analyses of anthocyanins (which contain hydrophobic aromatic rings) in wine and grape samples.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently used matrices are derivatives of benzoic acid, e.g., 2,5-dihydroxybenzoic acid (2,5-DHB; Juhasz et al 1993;Carpentieri et al 2007) and derivatives of cinnamic acid, e.g., α-cyano-4-hydroxycinnamic acid (CHCA) or sinapic acid (SA). Fullerenes have also been used as matrices, whereas the first application was for laser desorption of biomolecules involving application of protein analyte solution directly onto the pre-deposited fullerene film (Michalak et al 1994). Fullerene matrices has been used for MALDI-TOF analysis of small hydrophobic molecules (e.g., steroids, fatty acids; Mernyak et al 2008, Mernyak et al 2009), but until now there are no data reported on their application for analyses of anthocyanins (which contain hydrophobic aromatic rings) in wine and grape samples.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, different matrix substances, such as porphyrins [12,13], inorganic material [14 -17], fullerene [18,19], and porous silicon [20], have also been used to eliminate matrix ion interference. Recently, carbon nanotubes as an alternative to conventional organic matrices were utilized successfully for low molecular mass analytes of peptides, organic compounds, and ␤-cyclodextrin [21].…”
mentioning
confidence: 99%
“…Michalak et al [17] discovered that C 60 fullerenes are suitable matrix candidates for protein analysis. This was confirmed by Huang et al [18] who used them for screening urine for diuretics.…”
Section: Introductionmentioning
confidence: 99%